A Postbilingual Zone? Language and Translation Policy in Toronto - Hébert, Lyse (Tusaaji: A Translation Review, 2017)
In Canada, translation has been conceptualized within multi-layered and interwoven historical and political processes of nation building. One strand of these processes is the country’s language policy, known as “official bilingualism”. This national construct is so entrenched that the Federal government has not perceived a need to pair Canada’s language laws with any legislation on translation. Despite this void, or perhaps because of it, the professional translation market first emerged as a corollary of official bilingualism, and it remains inflected by its a priori, which have also driven the design of university translator training programs. In giving English and French preferred status over all other “minority” languages that once were (i.e. Indigenous languages) and/or might become (i.e. Ukrainian, Spanish, Chinese, Arabic, Urdu, etc.) vehicular languages in certain regions or cities, public policy, which includes content and funding of university programs, has also restricted translator training to “official languages”. This paper presents some preliminary data from a project aimed at proposing models for “post-bilingual” language and translation policies. More precisely, it focuses on one of Canada’s most linguistically heterogeneous spaces–Toronto–and its multilingual translation policy. Drawing on González Núñez’ adaptation of Spolsky’s language planning model, I argue in favour of a new set of language and translation policies that countenance disparate and, at times, contradictory linguistic realities across and within Canada’s post-bilingual zones, foregrounding elements that might inform evidence-based policies. Also informed by language rights research (e.g. De Schutter), this paper also serves as a preliminary discussion of language and translation policies that might be the springboard for new models of translator training that would ensure equal access to translation services for speakers of minority languages.